LEGAL LIABILITY OF INFLUENCERS FOR MISLEADING PRODUCT INFORMATION IN DIGITAL CONSUMER PROTECTION IN ELECTRONIC TRANSACTIONS - Ratih Manggar Sari; Ariy Khaerudin; Ismiyanto (PT. Radja Intercontinental Publishing, 2026)
The rapid growth of social media has made influencers key actors in digital marketing, significantly affecting consumer purchasing decisions. However, misleading product information, exaggerated claims, and the failure to disclose paid partnerships have raised important legal concerns and weakened consumer protection. This study analyzes the legal status of influencers as subjects of legal liability, examines their responsibility for disseminating misleading information in electronic transactions, and compares Indonesia's legal framework with those of the United States and the European Union. Using normative legal research with statutory, conceptual, and comparative approaches, the study recommends stronger regulations, clearer disclosure obligations, and enhanced legal accountability for influencers.